Did cryptocurrencies exhibit log‐periodic power law signature during the second wave of COVID‐19?. (21st September 2022) - Ghosh, Bikramaditya; Papathanasiou, Spyros; Pergeris, Georgios
Abstract: Many studies have associated cryptocurrencies with bubbles, especially during stressed market conditions such as the recent outbreak of the second wave of COVID‐19. Although the majority of studies have focused on Bitcoin, we investigate the predictability of bubble formation in the cryptocurrency market by using the log‐periodic power law and we uncover some important stylized facts of this market. Our sample consists of data for a selection of 15 cryptocurrencies for the period between 1 January 2021 and 1 September 2021 which coincides with the second wave of COVID‐19. We analyse 86 speculative bubbles, and we find that the cryptocurrency market has three times higher drawdown over equities during stressed market conditions.